The effect of oxygenated turpentine oil additive in diesel fuel on the performance and emission characteristics in one-cylinder di engines - Kadarohman, Asep; Khoerunnisa, Fitri; Syazwana, Sapee; Sardjono, Ratnaningsih Eko; Izuan, Izzudin; Hendrawan, .; R., Mamat; Ahmad Fitri, Yusop; Erdiwansyah, .; Yusaf, Talal (MDPI, 2021)
A study on the application of oxygenated turpentine oil as a bio-additive in diesel fuel was conducted. The purpose of this research was to investigate the effect of oxygenated turpentine oil additive in diesel fuel on the performance and emission characteristics in diesel engines. Oxygenated turpentine oil is obtained from the oxidation process of turpentine oil. In this experimental study, the influences of oxygenated turpentine oil-diesel blended fuel OT0.2 (0.2% vol oxygenated turpentine oil and 99.8% vol diesel) were compared with pure diesel on engine performance, and emission characteristics were examined in a one-cylinder four-stroke CI engine. The test was performed at two engine loads (25% and 50%) and seven engine speeds (from 1200–2400 rpm with intervals of 200 rpm). The physiochemical characteristics of test fuels were acquired. The engine indicated power, indicated torque, fuel flow rate, and emissions (carbon dioxide, CO2; carbon monoxide, CO; and nitrogen oxide, NOX ) were examined. The results revealed that the engine power shows slight increments of 0.7–1.1%, whereas the engine torque slightly decreased with oxygenated turpentine usage compared to pure diesel in most conditions. Furthermore, a reduction in NOX emission decreased by about 0.3–66% with the addition of oxygenated turpentine in diesel compared to diesel. However, usage of OT0.2 decreased fuel flow rate in most speeds at low load but gave a similar value to diesel at 50% load. CO emissions slightly increased with an average of 1.2% compared to diesel while CO2 emissions increased up to 37.5% than diesel. The high-water content, low cetane number, and low heating value of oxygenated turpentine oil were the reasons for the inverse effect found in the engine performances.